Biomechanical evaluation of 3-unit fixed partial dentures on monotype and two-piece zirconia dental implants. Issue 3 (17th February 2022) - de Matos, Jefferson David Melo; Lopes, Guilherme da Rocha Scalzer; Nakano, Leonardo Jiro Nomura; Ramos, Nathália de Carvalho; Vasconcelos, John Eversong Lucena de; Bottino, Marco Antonio; Tribst, João Paulo Mendes
Abstract: This study aimed to evaluate the biomechanical behavior, stress distributions and bone microstrain of fixed partial dentures (FPD) with ceramic abutments supported on monotype zirconia implants, titanium implants and two-piece zirconia implants, using finite element analysis. A three-dimensional model of the jaw was simulated containing 1.0 mm thick cortical bone and cancellous bone tissue. A FPD and implant models (4.1 x 10 mm) were modeled containing a cement-retained implant abutment. These models were replicated in three groups with similar geometries: Titanium Implant and Zirconia Abutment (Ti-Zr); Zirconia Implant and Zirconia Abutment (Zr-Zr) and Monotype Zirconia Implant (Zr-S). An axial load of 300 N was applied to the center of the first premolar. The microstrain (με) and the Von-Mises stress (MPa) were assumed as failures criteria. For the three groups, a higher stress concentration was observed in the region of FPD connectors. The Ti-Zr group showed a higher stress concentration in the prosthesis and implant when compared to the other groups. However, the smaller elastic modulus of the titanium implant, in relation to the zirconia, provided a lower stress in the abutment and in the prosthetic screw. The monotype implant system allowed a more homogeneous stress distribution and its strain were predominantly located in the cervical region of the peri-implant bone tissue. Monotype or two-piece zirconia implants can be used for rehabilitation with FPD. However, the absence of separation between implant and abutment in the monotype system avoids the stress concentration in the prosthetic screw and reduced the peri-implant bone strain.